Nucleobase Modifiers Identify TET Enzymes as Bifunctional DNA Dioxygenases Capable of Direct N‐Demethylation. (11th May 2020) - Ghanty, Uday; Wang, Tong; Kohli, Rahul M.
Abstract: TET family enzymes are known for oxidation of the 5‐methyl substituent on 5‐methylcytosine (5mC) in DNA. 5mC oxidation generates the stable base 5‐hydroxymethylcytosine (5hmC), starting an indirect, multi‐step process that ends with reversion of 5mC to unmodified cytosine. While probing the nucleobase determinants of 5mC recognition, we discovered that TET enzymes are also proficient as direct N‐demethylases of cytosine bases. We find that N‐demethylase activity can be readily observed on substrates lacking a 5‐methyl group and, remarkably, TET enzymes can be similarly proficient in either oxidation of 5mC or demethylation of N4‐methyl substituents. Our results indicate that TET enzymes can act as both direct and indirect demethylases, highlight the active‐site plasticity of these Fe II /α‐ketoglutarate‐dependent dioxygenases, and suggest activity on unexplored substrates that could reveal new TET biology. Abstract : TET family enzymes are robust and direct N‐demethylases, and this activity is comparable to its normal activity in the oxidation of 5‐methylcytosine, as determined using a nucleobase‐modification strategy. This remarkable N‐demethylase activity highlights the plasticity of the TET active site and suggests broader biological roles for TET enzymes beyond impacting DNA‐methylation dynamics.